EU Mobility - Jo Ritzen; Martin Kahanec; Jasmina Haas (Institute of Labor Economics (IZA), 2017)
The free movement of people and of workers (intra EU mobility) is one of the corner-stones of the EU. It has overwhelmingly benefitted the citizens of the EU member states both in the countries of work and in the countries of origin. Earlier apprehensions on crowding out of less educated workers in the countries of destination and on welfare migration turned out to be by and large refuted. At the same time, EU mobility policies still need a significant deepening and upgrading, to deal with special cases of crowding out in subsectors and with fraudulent contracts. Full integration of some groups of mobile EU workers is difficult because of linguistic and cultural barriers. There is a new challenge for EU policy: integration of circular mobile migrants. EU countries should be guided by the EU to cut red tape and harmonize administration.
Keywords: J15; J61; J68; 330; EU enlargement; free movement of workers; labor mobility; migration policy; European Single Market; labor adjustment; stabilization; vibrant Europe